2019
DOI: 10.1002/jbm.a.36696
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of in vitro cytotoxicity and properties of polydimethylsiloxane‐based polyurethane/crystalline nanocellulose bionanocomposites

Abstract: Polydimethylsiloxane‐based polyurethane (PU)/crystalline nanocellulose (CNC) bionanocomposites were produced via in situ prepolymer approach. Also, hexamethylene diisocyanate as aliphatic diisocyanate monomer and 1,4‐butanediol as aliphatic chain extender were used. CNC was incorporated into PU matrix to prepare different PU/CNC bionanocomposites. Effect of CNC content on the properties of the bionanocomposites such as thermal, thermophysical, microstructure, and in vitro cytotoxicity was investigated. Accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…It is observed that on sample set (1), cell viability increases as much as 3.7% when loading of c-CNF increases from 0 to 5 wt%. This finding shows good agreement with work conducted by Khadivi et al [90]. Next, by increasing the molecular weight of H 2 N-PDMS-H 2 N from 1000 to 4000 with fixed 5 wt% c-CNF, the finding shows increase in cell viability value by as much as 23.1%.…”
Section: Cellulose As Versatile Fibersupporting
confidence: 92%
See 1 more Smart Citation
“…It is observed that on sample set (1), cell viability increases as much as 3.7% when loading of c-CNF increases from 0 to 5 wt%. This finding shows good agreement with work conducted by Khadivi et al [90]. Next, by increasing the molecular weight of H 2 N-PDMS-H 2 N from 1000 to 4000 with fixed 5 wt% c-CNF, the finding shows increase in cell viability value by as much as 23.1%.…”
Section: Cellulose As Versatile Fibersupporting
confidence: 92%
“…In fact, it is reported that with the addition of nanocellulose, the nanocomposite film obtained will have a better cytotoxicity level. As reported by Khadivi et al [90], concentration of viable cells increases as reinforced CNC loading increases on polydimethylsiloxane-(PDMS-) based PU nanocomposite films. The CNC was incorporated using the prepolymer method.…”
Section: Cellulose As Versatile Fibermentioning
confidence: 58%
“…At the end of the incubation period, the MTT solution was removed and the cultures were solubilized in 1 ml acidic isopropanol (0.04 M HCl in absolute isopropanol) and centrifuged at 1,300 rpm for 2 min. Finally, the absorbance of the supernatant was measured at 570 nm (Khadivi, Salami‐Kalajahi, & Roghani‐Mamaqani, ; Torkpur‐Biglarianzadeh & Salami‐Kalajahi, ). The same procedure was conducted without using dendrimers and drugs as blank sample.…”
Section: Methodsmentioning
confidence: 99%
“…[ 18 ] As an example, the shear force applied on polymer melt is a prominent factor on dispersion of CNT [ 19 ] and chain disentanglement of polyurethane [ 20,21 ] in the melt mixing method, where the polymer melt with higher viscosity results in higher mixing energy input. [ 20 ] Polyurethane‐based nanocomposites showed higher mechanical characteristics, barrier properties, [ 22 ] abrasion resistance, [ 23,24 ] and thermal stability, [ 25–28 ] compared with their neat matrix. Carbon nanotube (CNT)/polyurethane composites combine the merits of CNT and the polyurethane matrix, and possess some special functions with regard to the conventional polyurethane composites.…”
Section: Introductionmentioning
confidence: 99%